2012
DOI: 10.1186/cc11475
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-induced hypercapnia in COPD: myths and facts

Abstract: During our medical training, we learned that oxygen administration in patients with chronic obstructive pulmonary disease (COPD) induces hypercapnia through the 'hypoxic drive' mechanism and can be dangerous. This mindset frequently results in the reluctance of clinicians to administer oxygen to hypoxemic patients with COPD. However, this fear is not based on evidence in the literature. Here, we will review the impact and pathophysiology of oxygen-induced hypercapnia in patients with acute exacerbation of COPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
143
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(162 citation statements)
references
References 12 publications
(16 reference statements)
7
143
1
6
Order By: Relevance
“…Consider the first pulse of this burst, which was during the period 0.004–3.58 s (Abdo et al 2009). The external forward shock should not exceed the observed average gamma‐ray flux ∼6.9 cm −2 s −1 (Abdo et al 2009) in energy band 50–300 keV. As the photon index was ∼0.58, the flux density at 300 keV was , which can be taken as a conservative f ν,lim .…”
Section: Case Study and A Comparison Of The Different Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consider the first pulse of this burst, which was during the period 0.004–3.58 s (Abdo et al 2009). The external forward shock should not exceed the observed average gamma‐ray flux ∼6.9 cm −2 s −1 (Abdo et al 2009) in energy band 50–300 keV. As the photon index was ∼0.58, the flux density at 300 keV was , which can be taken as a conservative f ν,lim .…”
Section: Case Study and A Comparison Of The Different Methodsmentioning
confidence: 99%
“…The optical afterglow showed that the deceleration time was less than 6 × 10 4 s (Greiner et al 2009). With E γ,iso ∼ 8.8 × 10 54 erg (Abdo et al 2009), we get the initial Lorentz factor Γ 0 > 90 using SP99.…”
Section: Case Study and A Comparison Of The Different Methodsmentioning
confidence: 99%
“…The other is the detection of the featureless Band‐type spectrum of GRB 080916C in a very wide energy range 8–13 GeV (Abdo et al 2009). If the GeV photons and the soft γ‐rays were from the same region, the bulk Lorentz factor of the emitting region Γ i has to be in the order of 10 3 and the emitting radius is R γ ∼ 2Γ 2 c δ t ∼ 6 × 10 15 cm (Γ i /10 3 ) 2 (δ t /0.1 s), where the typical variability time‐scale δ t is measured in the local frame of the burst (Abdo et al 2009; Zou, Fan & Piran 2009) and c is the speed of light. For such a large R γ , the widely discussed photosphere model of GRBs (Thompson 1994; Rees & Mészáros 2005; Pe'er, Mészáros & Rees 2006) failed.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare providers should pay careful attention administering the oxygen therapy in patients with COPD or other known risk factors that can predispose to hypercapnic respiratory failure with acidosis [2,3]. For this subgroup of patients, a target saturation range of 88-92% is recommended to avoid hypoxemia and reduce the risk of oxygen-induced hypercapnia [2][3][4].…”
Section: Oxygen Therapymentioning
confidence: 98%
“…For this subgroup of patients, a target saturation range of 88-92% is recommended to avoid hypoxemia and reduce the risk of oxygen-induced hypercapnia [2][3][4]. Therefore, oxygen saturation should be monitored continuously and the patient's further treatment should be guided by the results of the arterial blood gas analysis [3].…”
Section: Oxygen Therapymentioning
confidence: 99%